Mobile Tigecycline Resistance: An Emerging Health Catastrophe Requiring Urgent One Health Global Intervention - Anyanwu, Madubuike Umunna; Nwobi, Obichukwu Chisom; Okpala, Charles Odilichukwu R.; Ezeonu, Ifeoma M. (Frontiers in Microbiology, 2022)
Mobile tigecycline resistance (MTR) threatens the clinical efficacy of the salvage antibiotic, tigecycline (TIG) used in treating deadly infections in humans caused by superbugs (multi-, extensively- and pandrug-resistant bacteria), including carbapenem- and colistin-resistant bacteria. Currently, non-mobile tet(X) and mobile plasmid-mediated transmissible tet(X) and resistance-nodulation-division (RND) efflux pump tmexCD-toprJ genes, conferring high-level TIG (HLT) resistance have been detected in humans, animals, and environmental ecosystems. Given the increasing rate of development and spread of plasmid-mediated resistance against the two last-resort antibiotics, colistin (COL) and TIG, there is a need to alert the global community on the emergence and spread of plasmid-mediated HLT resistance and the need for nations, especially developing countries, to increase their antimicrobial stewardship. The spread of MTR, essentially, has One Health ramifications and portends a monumental threat to global public and animal health as it could lead to outrageous health and economic impact due to limited options for therapy. This current study, therefore, discussed why MTR is an emerging health catastrophe requiring urgent One Health global intervention. Specifically, this review has been constructed as follows: (a) antimicrobial activity of tigecycline; (b)mechanism of tigecycline resistance; (c) distribution, reservoirs, and traits of MTR gene-harbouring isolates; (d) causes of MTR development; (e) possible MTR gene transfer mode and One Health implication; and (f) MTR spread and mitigating strategies.